2016
DOI: 10.4049/jimmunol.1600407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel CD4+ T Cell Subsets in the Target Tissue of Sjögren’s Syndrome and Their Differential Regulation by the Lymphotoxin/LIGHT Signaling Axis

Abstract: Despite being one of the most common rheumatologic diseases, there is still no disease-modifying drug for primary Sjögren's syndrome (pSS). Advancing our knowledge of the target tissue has been limited by the low dimensionality of histology techniques and the small size of human salivary gland biopsies. In this study, we took advantage of a molecularly validated mouse model of pSS to characterize tissue-infiltrating CD4 T cells and their regulation by the lymphotoxin/LIGHT signaling axis. Novel cell subsets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…The second limitation resides in the duration of the study which was terminated when mice reached 16 weeks of age. At this time-point, NOD mice have a well-established immune infiltration that is stable in terms of cellular composition and number of infiltrating cells [36]. Nonetheless, one cannot exclude that longer exposure to increased BAFF levels could further increase the frequency and number of GC B cells within the glandular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second limitation resides in the duration of the study which was terminated when mice reached 16 weeks of age. At this time-point, NOD mice have a well-established immune infiltration that is stable in terms of cellular composition and number of infiltrating cells [36]. Nonetheless, one cannot exclude that longer exposure to increased BAFF levels could further increase the frequency and number of GC B cells within the glandular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed at answering this question using the NOD mouse model of pSS, which is one of the best-studied and validated models of pSS [41]. Specifically, integrated analysis of publically-available mouse and human pSS datasets showed that 58% of the human pSS transcriptional gene signature (derived from the analysis of parotid and minor salivary glands from pSS patients) was upregulated in the target tissue from 16-week old male NOD mice [36], indicating that the NOD strain is a relevant model to study the human disease from a molecular standpoint. Nonetheless, this model does not recapitulate all features of the human disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass cytometry has been used to characterize immune subsets in the target tissue and blood of both mouse models of Sjögren’s syndrome and patients with primary Sjögren’s syndrome [9, 10]. RNA-Seq transcriptomic analyses were reported in various diseases, such as Crohn’s disease, renal injury, chronic periodontitis, and many others [1114].…”
Section: Introductionmentioning
confidence: 99%